PkM Edukasi PHBS dan Social Distancing Pada Masa Pandemi di Ponpes KH Murodi Mranggen Demak - Sunan Baedowi; Ikha Listyarini; Kiswoyo; Moh. Aniq KHB (Kanigara, 2021)
Corona virus not only has an impact on health but also various other aspects of life. How to prevent and avoid the corona virus can be done with clean and healthy behavior (PHBS) and social distancing. The purpose of the PKM Educational PHBS and Social Distancing activities during the Pandemic Period at Ponpes K.H. Murodi Mranggen Demak is to improve the knowledge and skills of the students in implementing clean and healthy living behavior (PHBS) and to practice self-discipline in implementing social distancing during the pandemic. The results of this activity on socialization and education are partners have been able to implement clean and healthy living behaviors and have implemented social distancing in an orderly and good manner. The conclusion of this activity is that various kinds of training need to be given to the community, although it may be considered that the training activities carried out are common, but in fact there are still people who do not understand.